2007
DOI: 10.1104/pp.107.097048
|View full text |Cite
|
Sign up to set email alerts
|

GIGANTEA Regulates Phytochrome A-Mediated Photomorphogenesis Independently of Its Role in the Circadian Clock

Abstract: (R.M., J.P.)GIGANTEA (GI) is a nuclear protein involved in the promotion of flowering by long days, in light input to the circadian clock, and in seedling photomorphogenesis under continuous red light but not far-red light (FR). Here, we report that in Arabidopsis (Arabidopsis thaliana) different alleles of gi have defects in the hypocotyl-growth and cotyledon-unfolding responses to hourly pulses of FR, a treatment perceived by phytochrome A (phyA). This phenotype is rescued by overexpression of GI. The verylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 71 publications
5
51
0
1
Order By: Relevance
“…It was constantly higher under LDs but lower under SDs. Together with the reduced miR172 abundance in the gi-2 mutant grown under LDs ( Figure 5B), these observations suggest that miR172 may be regulated by a clock-independent GI pathway (Mizoguchi et al, 2005;Oliverio et al, 2007).…”
Section: Mir172 Abundance Is Altered In Gi-2 and Photoreceptor Mutantsmentioning
confidence: 73%
“…It was constantly higher under LDs but lower under SDs. Together with the reduced miR172 abundance in the gi-2 mutant grown under LDs ( Figure 5B), these observations suggest that miR172 may be regulated by a clock-independent GI pathway (Mizoguchi et al, 2005;Oliverio et al, 2007).…”
Section: Mir172 Abundance Is Altered In Gi-2 and Photoreceptor Mutantsmentioning
confidence: 73%
“…Interestingly, we detected no significant relationship between GI expression and flowering in the NILs, despite an important function of GI being the promotion of flowering through the regulation of CONSTANS (CO) (45,46). GI regulates diverse traits through distinct molecular pathways (47)(48)(49), and it is possible that these pathways are not all equally sensitive to precise changes in GI expression. GI-mediated promotion of flowering might be more robust than growth to small perturbations of GI expression and function, an idea supported by a previous study in which an induced mutation of GI altered growth but not GI-dependent promotion of CO (48).…”
Section: Precise Changes In the Waveform Of Gi Expression Are Sufficimentioning
confidence: 80%
“…However, loss-of-function mutants also show an increased hypocotyl elongation under R and B light (Fowler et al, 1999;Park et al, 1999;Huq et al, 2000;Martin-Tryon et al, 2007). Recently, GI has been implicated in many VLFR, but not in HIR under continuous FR light (Oliverio et al, 2007). The involvement of brassinosteroids as positive regulators in the phytochrome signaling cascade was established by the analysis of deetiolated2 and the identification of the brassinosteroid biosynthesis mutant diminuto/dwarf1 as an enhanced very-low-fluence response1 mutant (Luccioni et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Pks1 and 2 mutants show enhanced phyA-mediated VLFR but are also involved in blue light-mediated phototropism (Lariguet et al, 2003(Lariguet et al, , 2006. Although GIGANTEA (GI) was first characterized as playing a role in the circadian clock and deetiolation under red light conditions, recent work showed that this protein is also important for hypocotyl growth, cotyledon opening, and germination under VLF conditions (Oliverio et al, 2007).…”
Section: Introductionmentioning
confidence: 99%